Analysis of Seabins Using Lightweight Concrete to Clean Up Plastic Waste on The Coast of Semayap Village, Kotabaru Regency - sylvina permata sari; Rahman Arifin (LPPM Institut Teknologi Adhi Tama Surabaya (ITATS), 2025)
The increasing plastic waste on the coast of Semayap Village poses a serious threat to the marine ecosystem and coastal community activities. Floating plastic pollutes the sea and disrupts fishing, tourism, and public health. An effective solution is using Seabin technology, as the area lacks a sustainable system to manage plastic waste. Current waste management remains conventional and relies on manual cleanups. This study used a literature review on Seabin technology and lightweight concrete, along with a field survey to assess coastal conditions in Semayap Village. It also involved modeling a suitable lightweight concrete structure to support the device. The results showed that the Seabin, made from lightweight concrete with pumice aggregate, weighs 105.46 kg, with a volume of 0.0628 m³ and density of 1,680 kg/m³, classifying it as lightweight concrete. It is 45.26 kg lighter than regular concrete, enhancing buoyancy and design efficiency with support from four 25-liter jerrycan floats. A 24-hour test at the Semayap coast captured 4.14 kg of surface waste, demonstrating its effectiveness, though performance can still be improved.